Free Polyethylenimine Enhances Substrate-Mediated Gene Delivery on Titanium Substrates Modified With RGD-Functionalized Poly(acrylic acid) Brushes - Mantz, Amy; Rosenthal, Alice; Farris, Eric; Kozisek, Tyler; Bittrich, Eva; Nazari, Saghar; Schubert, Eva; Schubert, Mathias; Stamm, Manfred; Uhlmann, Petra; Pannier, Angela K. (Frontiers in Chemistry, 2019)
Substrate mediated gene delivery (SMD) is a method of immobilizing DNA complexes to a substrate via covalent attachment or nonspecific adsorption, which allows for increased transgene expression with less DNA compared to traditional bolus delivery and may increase cells receptivity to transfection via cell-material interactions. Substrate modifications with poly(acrylic) acid (PAA) brushes may improve SMD by enhancing substrate interactions with DNA complexes via tailored surface chemistry and increasing cellular adhesion via moieties covalently bound to the brushes. Previously, we described a facile method to graft PAA brushes to Ti and further demonstrated conjugation of cell adhesion peptides (i.e. RGD) to the PAA brushes to improve biocompatibility. The objective of this work was to investigate the ability of Ti substrates modified with PAA-RGD brushes (PAA-RGD) to immobilize complexes composed of branched polyethyleneimine and DNA plasmids (bPEI-DNA) and support SMD in NIH/3T3 fibroblasts. Transfection in NIH/3T3 cells cultured on bPEI-DNA complexes immobilized onto PAA-RGD substrates was measured and compared to transfection in cells cultured on control surfaces with immobilized complexes including Flat Ti, PAA brushes modified with a control peptide (RGE), and unmodified PAA. Transfection was 2-fold higher in cells cultured on PAA-RGD compared to those cultured on all control substrates. While DNA immobilization measured with radiolabeled DNA indicated that all substrates (PAA-RGD, unmodified PAA, Flat Ti) contained nearly equivalent amounts of loaded DNA, ellipsometric measurements showed that more total mass (i.e. DNA and bPEI, both complexed and free) was immobilized to PAA and PAA-RGD compared to Flat Ti. The increase in adsorbed mass may be attributed to free bPEI, which has been shown to improve transfection. Further transfection investigations showed that removing free bPEI from the immobilized complexes decreased SMD transfection and negated any differences in transfection success between cells cultured on PAA-RGD and on control substrates, suggesting that free bPEI may be beneficial for SMD in cells cultured on bPEI-DNA complexes immobilized on PAA-RGD grafted to Ti. This work demonstrates that substrate modification with PAA-RGD is a feasible method to enhance SMD outcomes on Ti and may be used for future applications such as tissue engineering, gene therapy, and diagnostics.